On the role of pin geometry in microstructure and mechanical properties of AA7075/SiC nano-composite fabricated by friction stir welding technique - Bahrami, Mohsen; Besharati Givi, Mohammad Kazem; Dehghani, Kamran; Parvin, Nader (Materials in engineering, 2014)
•AA7075/SiC nano-composite was fabricated in stir zone via FSW.•Using triangular pin tool resulted in the highest tensile strength.•In exception of four-flute cylindrical specimens, all specimens fractured from base metal.•Threaded tapered specimen showed the most uniform distribution of SiC particles. The main purpose of this research is to investigate the influence of pin geometry on the macrostructure, microstructure and mechanical properties of the friction stir welds, reinforced with SiC nano-particles. Toward this end, friction stir welding (FSW) conducted using five geometrically different pin tools. Other welding parameters were remained unchanged. Microstructural evaluation using optical microscopy (OM) and scanning electron microscopy (SEM) revealed a banded structure consisting of particle-rich and particle-free regions in stir zone (SZ). The most uniform particle distribution was found in the case of using threaded tapered pin tool. On the other hand, it was discovered that the reinforcements had severely accumulated in the SZ of specimen friction stir welded (FSWed) with four-flute cylindrical pin tool. Moreover, threaded tapered and four-flute cylindrical specimens showed the highest and the lowest microhardness, respectively. In spite of four-flute cylindrical specimen, other specimens failed in base metal during tensile testing. Besides, the highest ultimate tensile strength (UTS) was recorded for the specimen FSWed with triangular pin tool. Fracture surface of tensile specimens were also studied employing SEM technique.